2002 Mount Beauty Workshop on Islam in Indonesia: Report - Hooker, Virginia; Ricklefs, M.C. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
The workshop invited each candidate to present her or his topic to colleagues. There followed debate and discussion about the topics, about conceptual complexities, and about the way in which the research of others shed light on each individual topic. Most of the students were at early stages of research (mostly in the first year of candidature), but three were at final stages (Syafi'i Anwar, Fatimah Husein and Saliy White). One candidate, Mohamad Hafiz, is working on the Syariah Court of Singapore. The discussions were vigorous and of great help to all participants.DOI: 10.15408/sdi.v10i1.642